Efektivitas Seduhan Daun Labu Siam dan Daun Salam Terhadap Peningkatan Kadar Hemoglobin pada Remaja Putri: The Effectiveness of Stewing Siamese Pumpkin Leaves and Stewing Bay Leaves on Increasing Hemoglobin Levels in Young Women - Nur Azizah Yusrin; Yustina Ananti; Yunri Merida (Journal of Health, 2023)
Background: Deficiency in hemoglobin levels is still a public health problem in Indonesia, including young women, caused by menstruation or heavy blood loss and a lack of iron and protein intake. According to World Health Organization data for 2022, globally the prevalence of anemia worldwide is 29.9% in women of childbearing age (15-49 years), the prevalence of deficiency in hemoglobin levels in Indonesia is 32%, the incidence rate in the Special Region of Yogyakarta is 19, 3% and the Sleman area as much as 22.86%. Objective: To determine the effectiveness of steeping chayote and bay leaves on increasing hemoglobin levels in female adolescents. Method: this study used a Quasi-Experimental Two Group Pretest-Postest Design. The subjects in this study were 40 young women who met the criteria. Data analysis used Wilcoxon test and Mann Whitney test. Results: The average Wilcoxon test before and after administration of chayote leaf infusion obtained a p-value of 0.003 <0.05, which means that there was a significant difference between before and after administration of bay leaf infusion with a p-value of 0.278 > 0.05 which means no there was a significant difference between before and after treatment. Based on the Mann Whitney test, the average after steeping chayote leaves and steeping bay leaves had a significant p value of 0.002 (0.002 <0.05) which showed a significant difference in the increase in hemoglobin levels in female adolescents. Conclusion: Infusion of chayote leaves is more effective than bay leaf infusion in increasing hemoglobin levels in female adolescents.